MODEL PENGEMBANGAN KOMPETENSI KOMUNIKATIF PEMBELAJARAN BAHASA JAWA SMA BERBASIS KONTEKS SOSIOKULTURAL - Sudi, Esti; Kurniadi, Endang (Lembaran Ilmu Kependidikan, 2007)
The insertion of javanese language in high schoolsÃ¢â¬â¢ curricula is one of theefforts to preserve it since the yaoung generation has practically no interest in thelanguage. The developmental design of the research wawws based on a qualitativeapproach. It was conducted in Banyumas, Pati, semarang, and Surakarta. Thoserepresent the diverse dialect of Javanese language. The respondents were the highschool teachers of Javanese language and their students. Data was gathered byobserving and ointerviewing them. Documentation was used to enrich the data whichlater was analized interactively. The result showed that the teaching of Javaneselanguage in high school has not been successful. The reason of the failure came fromthe teachers who had no previous Javanese competence background. Based on thefindings, the researcher developed a guide book which leads the teachers to makeappropriate preparation to teach the communicative competence in Javanese. Thepreparation must be based on socio cultural context of each dialect.Kata kunci: kompetensi komunikatif, konteks sosiokultural, bahasa Jawa